A systematic review of associations between nutritional status, physical fitness, and learning motivation and physical education learning outcomes - Randi Asmilyadi; Kamal Firdaus; Aldo Naza Putra; Nugroho Susanto (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
We applied the four-domain FICO framework (Focus, Information, Context, Outcome) for quality appraisal. Because the included designs were highly heterogeneous (cross sectional, experimental, quasi experimental, and qualitative), we opted for a narrative/thematic synthesis rather than a meta analysis. A single reviewer team handled screening and eligibility decisions, with no second independent rater, so we do not report inter rater reliability statistics. This limitation is addressed in Section 5.5.. Of the 622 initial records, 50 studies met the inclusion criteria after screening and eligibility assessment. The studies covered 26 countries, but mostly from Spain, Australia, the United States, Indonesia and Ireland, which also had the most references to the legislative papers, were mostly cross-sectional quantitative studies with some experimental, quasi-experimental and qualitative designs. The results showed that autonomous and intrinsic motivation were the best predictors of engagement and learning outcomes; physical fitness, motor skills, motivation, and physical activity in students were strongly linked together; student-centered and technology-supported pedagogies were effective in establishing motivational climates; and, nutritional status, generally considered as a contextual factor affecting fitness-related outcomes, was rarely the central variable. These findings align with self-determination and expectancy-value theories and stress the need for health-related fitness and motivational pedagogy to be integrated into PE curricula. Still, the review found very few longitudinal studies, hardly any focus on the nutritional status, and quite a few inconsistent definitions of learning outcomes. Going forward, research should include longitudinal and intervention designs that concurrently explore nutritional status, physical fitness, and motivation, all using standardized outcome measures in order to improve cross-study comparisons and meta-analytic synthesis.